Transcriptional Remodeling Patterns in Murine Dendritic Cells Infected with Paracoccidioides brasiliensis: More Is Not Necessarily Better - Calliandra M. de-Souza-Silva; Fabián Andrés Hurtado; Aldo Henrique Tavares; Getúlio P. de Oliveira; Taina Raiol; Christiane Nishibe; Daniel Paiva Agustinho; Nalvo Franco Almeida; Maria Emília Machado Telles Walter; André Moraes Nicola; Anamélia Lorenzetti Bocca; Patrícia Albuquerque; et al. (Journal of Fungi, 2020)
Most people infected with the fungus Paracoccidioides spp. do not get sick, but approximately 5% develop paracoccidioidomycosis. Understanding how host immunity determinants influence disease development could lead to novel preventative or therapeutic strategies; hence, we used two mouse strains that are resistant (A/J) or susceptible (B10.A) to P. brasiliensis to study how dendritic cells (DCs) respond to the infection. RNA sequencing analysis showed that the susceptible strain DCs remodeled their transcriptomes much more intensely than those from the resistant strain, agreeing with a previous model of more intense innate immunity response in the susceptible strain. Contrastingly, these cells also repress genes/processes involved in antigen processing and presentation, such as lysosomal activity and autophagy. After the interaction with P. brasiliensis, both DCs and macrophages from the susceptible mouse reduced the autophagy marker LC3-II recruitment to the fungal phagosome compared to the resistant strain cells, confirming this pathway’s repression. These results suggest that impairment in antigen processing and presentation processes might be partially responsible for the inefficient activation of the adaptive immune response in this model.